FAO International Code of Conduct for pesticides - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
With the cooperation of the agrochemical industry and other international institutions, the FAO has prepared a o voluntary international Code of Conduct on the 'Distribution and Use of Pesticides'. It has now been adopted and member nations have...